Pelatihan Pemanfaatan Teknologi Dalam Pembelajaran - Fathahillah; Syahrul; Abdul Muis Mappalotteng; Gufran Darma Dirawan; Ayu Lestari; Saharuna (Jurusan Teknik Informatika dan Komputer, 2023)
The partner of the Community Partnership Program (PKM) is the teachers in SMP Takalar District. The problem identified is that the junior high school teachers in Takalar District still face challenges in creating interactive learning media that are suitable for their teaching methods. This is due to a lack of technological skills in developing instructional media. The existing sources of interactive media are limited, both in terms of material compatibility and the preferences and teaching styles of the teachers. This training aims to enhance the understanding and skills of the teachers in developing interactive learning materials by utilizing technology. The method applied in this training is the descriptive method. The stages involved include lectures, discussions and Q&A sessions, exercises, mentoring, demonstrations, and evaluation of the developed learning materials. The expected outcome of this training is that the teachers will be able to improve their skills in creating interactive learning media that align with their needs and teaching styles.